Impacto socio económico sustentable y sostenible de la agricultura vertical en el Ecuador - Cabello Orellana, Delia Christel (2024)
Vertical farming is an engineering technique that uses vertical space to grow food in a controlled area, increasing production in a small area. The main objective is to provide sustainable and efficient solutions to the growing demand for food in urban areas with limited resources. This approach can improve food security, especially in urban and low-income groups, by providing fresh, organic food without chemicals or toxins. Vertical farming aims to increase food production by optimizing the use of land and resources while reducing dependence on climate and environmental conditions. The technologies used include the use of hydroponic systems and new agricultural techniques that allow year-round harvesting in urban environments. The main results of vertical farming are 95% less water use and 99% less land use compared to traditional agriculture. Additionally, it reduces emissions by reducing the need to transport food and avoiding the use of pesticides, making production cleaner and more efficient. But challenges include high implementation costs and the need for modern technology, as well as waste issues and potential impacts on traditional farmers. In conclusion, vertical farming is a viable solution to food security and sustainability problems, although its success depends on overcoming technical and economic challenges.